Highway drainage guidelines (American Association of State Highway and Transportation Officials, 2007)
The Highway Drainage Guidelines provides a consolidated overview of highway hydraulic design and discusses possible hydrology problems in the following areas: Hydraulic Considerations in Highway Planning and Location; Hydrology; Erosion and Sediment Control in Highway Construction; Hydraulic Design of Highway Culverts; The Legal Aspects of Highway Drainage; Hydraulic Analysis and Design of Open Channels; Hydraulic Analysis for the Location and Design of Bridges; Hydraulic Aspects in Restoration and Upgrading of Highways; Storm Drain Systems; Evaluating Highway Effects on Surface Water Environments; Highways Along Coastal Zones and Lakeshores; Stormwater Management; Training and Career Development of Hydraulics Engineers; Culvert Inspection, Material Selection, and Rehabilitation; Guidelines for Selecting and Utilizing Hydraulics Engineering Consultants.